RESULTS OF THE STUDY OF COMPARATIVE ANALYSIS OF THE DEVELOPMENT OF COMPLICATIONS AFTER COVID-19 VACCINATION WITH DIFFERENT GROUPS (TYPES) OF VACCINES IN THE PRESENCE OF CONCOMITANT CHRONIC DISEASES IN MEN OF DIFFERENT AGES OF THE POPULATION OF THE FERGANA - Todzhikhazhaev, Shoyadbek; Mamarasulova, Dilfuza (Medical science of Uzbekistan, 2025)
Relevance. The study of the post-COVID state among the vaccinated population of Uzbekistan is important to determine the risk factors characteristic of the local population, as well as to identify the characteristics of the course of the disease and effective preventive strategies in remote areas such as the Fergana Valley. Objective. The objective was to study the preventive strategy in the development of complications after vaccination with Covid-19 with various vaccines in healthy residents and residents with concomitant chronic diseases in different age groups. Materials and methods of research. The work was carried out on the basis of the Andijan State Medical Institute using the registry of patients belonging to the family clinic No. 8. population of the Fergana Valley who had COVID-19. The analyzed population: The sample includes men of different age groups, as well as people with different chronic diseases to take into account risk factors. The age groups of residents were divided into 18-30 years (young), 31-50 years (adults), 50 to 60 years (elderly), 65 and over 65 years (old people). These age groups of participants consisted of 10,835 healthy and 19,006 patients with Covid-19. Results. Analysis of the results showed that the manifestation of AEFI in this group of residents developed regardless of age. Thus, even in the group of young healthy men aged 18-50, complications from all types of vaccines were encountered. The highest percentage (99.4%) of the absence of complications in healthy men was noted in the group of residents aged 18-50. Conclusion. Effective monitoring of the epidemiological situation and the health status of vaccinated patients with post-COVID syndrome plays a key role in the development of timely and effective measures.